2021
DOI: 10.31004/basicedu.v5i5.1326
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Aplikasi Google Classroom dalam Meningkatkan Efektivitas Belajar Mahasiswa Berbasis Daring di Masa Pandemik Covid-19

Abstract: Akibat dari pandemik covid-19 membuat sistem belajar dari berbasis konvensional menjadi berbasis daring. Google Classroom menjadi salah satu aplikasi khusus yang digunakan untuk pembelajaran daring yang dapat dilakukan dari jarak jauh sehingga memudahkan dosen dan mahasiswa untuk membuat, mengelompokan dan membagikan tugas, selain itu dosen dan mahasiswa bisa setiap saat melakukan kegiatan pembelajaran melalui ruang kelas Google Classroom. Tujuan dari penelitian ini adalah untuk mengetahui efektivitas belaja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
1
3
0
7
Order By: Relevance
“…The findings in the present study prove that Google classroom is not only effective for supporting the online learning in secondary and tertiary levels [6], [7], [9], [10], [45], but also helpful for engaging students of primary level and facilitating the teachers. The results demonstrate positive perceptions towards the use of Google Classroom which support the previous findings on the benefits and challenges of this web-based platform [10], [32], [46]- [48].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The findings in the present study prove that Google classroom is not only effective for supporting the online learning in secondary and tertiary levels [6], [7], [9], [10], [45], but also helpful for engaging students of primary level and facilitating the teachers. The results demonstrate positive perceptions towards the use of Google Classroom which support the previous findings on the benefits and challenges of this web-based platform [10], [32], [46]- [48].…”
Section: Discussionsupporting
confidence: 62%
“…Further research was conducted in online English classes and the findings indicate that the application of Google Classroom has been successful to enhance students' involvement in virtual discussions, reduce the psychological obstructions, increase learning attention, and improve learning motivation in terms of sharing ideas and comment in chatting column [6]. An investigation on the university students' view toward the effectiveness of using Google Classroom as media for facilitating learning during Covid-19 pandemic also suggested that Google Classroom has been effective for its easiness of doing course assignments, usefulness of developing ICT skills and practicality of identifying learning result quickly [8]. Furthermore, the findings in Tangerang Selatan (North Tangerang), a district in West Java, showed that high school teachers admit that Google Classroom is useful to assist teachers in organizing students' assignments, managing classes, and supporting students' engagements [39].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Penelitian juga menjelaskan bahwa pembelajaran daring lebih efektif dan efisien dikarenakan siswa bisa lebih leluasa untuk mempelajari materi pelajaran yang dilakukan secara mandiri. Selain itu, penelitian (Marbun & Sinaga, 2021) juga menunjukkan bahwa mahasiswa yang belajar daring melalui aplikasi google classroom bisa meningkatkan efektivitas belajarnya seperti kemudahan dalam mengerjakan tugas, terampil menggunakan sarana teknologi dan informasi sehingga bisa dengan cepat mengetahui hasil belajarnya.…”
Section: Kesimpulanunclassified
“…In addition, another option that can be used as an online learning platform is Google Classroom. The use of this platform can increase the effectiveness of learning (Marbun & Sinaga, 2021), through the use of which students and teachers are accommodated to carry out the learning process flexibly so that students' learning motivation can be increased (Destyana & Surjanti, 2021). In general, students think that this platform is effective and efficient and interesting if it is integrated into the learning process (Harefa & Sumiyati, 2020).…”
Section: Introductionmentioning
confidence: 99%